Skill Deficiencies in Students and B-School Interventions : A Qualitative Study Exploring the Perceptions of Leader - Directors - Bhatnagar, Neha (Prabandhan: Indian Journal of Management, 2020)
This paper explored the perceptions of Indian B-school (business school) directors about the lack of skills among the students and how various interventions at B-schools help students in skill development. The interviews were conducted and the thematic analysis of the interview transcripts was done with the help of QSR Nvivo 11 Pro. The results suggested that the skills lacking in the students at the time of joining an MBA (Master of Business Administration) programme were ethical behavior, discipline, dexterity to work, communication skills, risk-taking abilities, innovation, and creativity. The B-school interventions to develop the skills of the students were found to be encouraging students to solve local problems using research skills, placement holidays to encourage creativity and innovation, teaching and learning through foreign university collaboration, orientation programmes, and skill labs. There was a gap in the literature, and none of the studies have explored the perceptions of Indian B-school directors about the entry-level skills of their students and the way MBA courses help graduates to become employable. This qualitative study was done to fill this research gap.